United States Of America Digital Diplomacy Against China Trade War - Anugrah Pardede, Julyo Paulus Putra; Putri, Penny Kurnia; Parameswari, A.A.A Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2023)
2018 has been a tense year in international trade because two superpower country on world economic, the US and China involved in a conflict known as the trade war. Various ways are taken by the US to win the trade war against China, one of which is by using digital diplomacy, digital diplomacy itself is a new concept in international relations. This research seeks to explain the United States digital diplomacy efforts against China by using qualitative research. The United States digital diplomacy against China in trade war has been successful so the United States can reduce international pressure on it, influence public perspectives, and legitimize its actions through the spread of posts on the Facebook and Twitter platforms by targeting national and international publics.